The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region - Kuhlmann, Michael; Proshchalykin, Maxim Yu. (Zootaxa, 2016)
Information about bees of the genus Colletes in the Caucasus region is summarized. Two new species are described from Azerbaijan: Colletes jovel Kuhlmann & Proshchalykin, sp. nov. and C. longimala Kuhlmann & Proshchalykin, sp. nov. Nine species are newly recorded from Caucasus: C. asiaticus Kuhlmann 1999, C. brevigena Noskiewicz 1936, C. cariniger Pérez 1903, C. glaber Warncke 1978, C. idoneus Cockerell 1922, C. inexpectatus Noskiewicz 1936, C. meyeri Noskiewicz 1936, C. schwarzi Kuhlmann 2002, and C. wahrmani Noskiewicz 1959. A total of 50 species are currently known from this area.